2021
DOI: 10.1155/2021/6636621
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1-Inhibitor AC-YVAD-CMK Inhibits Pyroptosis and Ameliorates Acute Kidney Injury in a Model of Sepsis

Abstract: Objective. To observe the protective effect of AC-YVAD-CMK on sepsis-induced acute kidney injury in mice and to explore its possible mechanisms primarily. Methods. Eighteen male C57BL/6 mice were randomly divided into sham-operated group (Control), cecal ligation and puncture group (CLP), and CLP model treated with AC-YVAD-CMK group (AC-YVAD-CMK) ( n = 6 in each group). Mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Neutrophil pyroptosis is a pro-inflammatory process mediated by GSDMD (Wen et al, 2022). Yang et al showed that neutrophils could secrete IL-1b through a CASP1dependent pathway, resulting in a higher mortality rate in mice (Yang et al, 2021). Sepsis could cause immune dysregulation and suppression of adaptive immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil pyroptosis is a pro-inflammatory process mediated by GSDMD (Wen et al, 2022). Yang et al showed that neutrophils could secrete IL-1b through a CASP1dependent pathway, resulting in a higher mortality rate in mice (Yang et al, 2021). Sepsis could cause immune dysregulation and suppression of adaptive immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the release of pro-inflammatory cytokine IL-1β appears to exacerbate the pro-inflammatory response and the spread of local tissue damage, which has been confirmed in a murine model of melioidosis ( 102 , 103 ). It was reported that IL-1β can be released by pyroptosis via the classical pathway, which lowers the murine survival rates ( 104 ). However, in 2014, Chen et al.…”
Section: Pyroptosismentioning
confidence: 99%
“…Recent research has confirmed the high expression of the active forms of caspase-1, GSDMD and inflammatory cytokines IL-1β and IL-18 in primary human TECs and LPS-induced mouse kidneys ( 107 ). The use of caspase-1 inhibitors can reduce the expression of NLRP1 inflammasome and the pyroptosis of TECs ( 108 ). By employing genetic and pharmacological methods, targeting the pyroptosis pathway can effectively reduce the expression and function of NLRP3 and GSDMD in sepsis-AKI ( 107 , 109 111 ).…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%